2021
DOI: 10.1016/j.ejor.2019.07.046
|View full text |Cite
|
Sign up to set email alerts
|

A personalized walking bus service requiring optimized route decisions: A real case

Abstract: Highlights• Definition of a new optimization problem: the Door-to-School Pedibus lines design.• The application arises from a real problem with high social and educational impact.• Line merging and dynamic capacity make the problem different from standard VRP.• Multiple solution methods proposed with no clear dominance.• Tested on both synthetic and real word scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Egli et al (2020)'s study on children's perspectives of walking routes to school in New Zealand has found that they are aware of both time and distance. All the previous studies in optimisation of WSB routes have considered this objective (Bolkhanian & Reyers, 2019; Tanaka et al, 2016; Tresoldi et al, 2021), that is, to minimise walking time .…”
Section: The Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Egli et al (2020)'s study on children's perspectives of walking routes to school in New Zealand has found that they are aware of both time and distance. All the previous studies in optimisation of WSB routes have considered this objective (Bolkhanian & Reyers, 2019; Tanaka et al, 2016; Tresoldi et al, 2021), that is, to minimise walking time .…”
Section: The Modelmentioning
confidence: 99%
“…The focus is, therefore, again on time using distance as a proxy variable. Time is the only factor considered in both Bolkhanian and Reyers (2019) and Tresoldi et al (2021), which is not sufficient to help realise all the potential benefits WSB might bring. Children love the experience of walking when it is enjoyable and they never complain about walking longer distances even though the WSB route is normally longer than the direct one (Heelan et al, 2008).…”
Section: Research Gaps In Walking-to-school Route Planning Problemmentioning
confidence: 99%
See 2 more Smart Citations